Diode laser‐induced tissue effects: In vitro tissue model study and in vivo evaluation of wound healing following non‐contact application. Issue 6 (16th May 2014) - Havel, Miriam; Betz, Christian S.; Leunig, Andreas; Sroka, Ronald
ABSTRACT Introduction The basic difference between the various common medical laser systems is the wavelength of the emitted light, leading to altered light–tissue interactions due to the optical parameters of the tissue. This study examines laser induced tissue effects in an in vitro tissue model using 1, 470 nm diode laser compared to our standard practice for endonasal applications (940 nm diode laser) under standardised and reproducible conditions. Additionally, in vivo induced tissue effects following non‐contact application with focus on mucosal healing were investigated in a controlled intra‐individual design in patients treated for hypertrophy of nasal turbinate. Methods A certified diode laser system emitting the light of λ = 1470 nm was evaluated with regards to its tissue effects (ablation, coagulation) in an in vitro setup on porcine liver and turkey muscle tissue model. To achieve comparable macroscopic tissue effects the laser fibres (600 µm core diameter) were fixed to a computer controlled stepper motor and the laser light was applied in a reproducible procedure under constant conditions. For the in vivo evaluation, 20 patients with nasal obstruction due to hyperplasia of inferior nasal turbinates were included in this prospective randomised double‐blinded comparative trial. The endoscopic controlled endonasal application of λ = 1470 nm on the one and λ = 940 nm on the other side, both in 'non‐contact' mode, was carried out as an outpatient procedure under local anaesthesia. The postoperative wound healing process (mucosal swelling, scab formation, bleeding, infection) was endoscopically documented and assessed by an independent physician. Results In the experimental setup, the 1, 470 nm laser diode system proved to be efficient in inducing tissue effects in non‐contact mode with a reduced energy factor of 5–10 for highly perfused liver tissue to 10–20 for muscle tissue as compared to the 940 nm diode laser system. In the in vivo evaluation scab formation following laser surgery as assessed clinically on endonasal endoscopy was significantly reduced on 1, 470 nm treated site compared to 940 nm diode laser treated site. Conclusions Diode laser system (1, 470 nm) induces efficient tissue effects compared to 940 nm diode laser system as shown in the tissue model experiment. From the clinical point of view, the healing process following non‐contact diode laser application revealed to be improved using 1, 470 nm diode laser compared to our standard diode laser practise with 940 nm. Lasers Surg. Med. 46:449–455, 2014. © 2014 Wiley Periodicals, Inc.